Interactive E-Module Development in Multimedia Learning - Nurhikmah H; Abdul Hakim; M. Syakir Wahid (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to develop interactive e-modules in the Multimedia Learning Course and to know the validity, practicality of the effectiveness of developing interactive e-modules in Multimedia Learning subject. This research method used Research and Development (R D), which focused on developing smartphone-based learning media, especially Android. The development model used the Alessi and Trollip development model, consisting of 3 stages: planning, design, and development. This research was conducted at Makassar State University with 45 students and one lecturer in multimedia learning. Interactive e-modules are used in multimedia learning courses to assist and facilitate lecturers in the learning process. Interactive e-modules were developed and validated by material experts and media experts, with the results of material validation obtained an average score of 4.9 (very valid) and media experts obtained an average score of 4.1 (valid) so that interactive e-modules can be tested in the field to determine the practicality and effectiveness with the results shown in the category of very practical and very effective. Based on the results found, it can be concluded that interactive e-modules are practical and effective in the learning process in multimedia learning courses at the Education Technology Study Program, Makassar State University